Chronic granulomatous inflammation caused by latent tuberculosis presented as a subcutaneous mass: A case report with review of literature - Hee Gyun Yang; Jungho Kim; Jung-Han Kim (IDCases)
Chronic granulomatous inflammation is a global disease caused by infection, auto-immune disease, toxic, or idiopathic factors. Pathological finding shows formation of distinct granulomas composed of aggregates of epithelioid macrophages, with a peripheral cuff of lymphocyte and plasma cells. Chronic granulomatous inflammation can occur in many different areas of the body, including the skin. Here, we report a case of a 64 years old woman who developed subcutaneous chronic granulomatous inflammation in the upper thigh, caused by latent tuberculosis. We also review granulomatous lesion in various countries with different incidence rate of tuberculosis and vascular feature, evaluating its effect when clinicians encounter.